ANALYSIS OF BIOMASS AND CARBON STOCK ON MANGROVE FOREST ECOSYTEM IN NORTH COASTAL AREA OF RUPAT ISLAND RIAU PROVINCE - Muhammad Sofyan; Aras Mulyadi; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Analysis of biomass and carbon stock on mangrove forest ecosytem in coastal area of North Rupat Riau Province has been conducted in January 2016. The method used in this study is a survey method with purposive sampling technique. The study showed that the potential mangrove biomass was directly proportional to mangrove carbon stocks. The average yield of biomass, carbon stocks of soil organic carbon and CO2 sequestration on mangrove forest was reserves amounted to 68,64 tons/ha , 904,75 tons/ha and 251,39 tons/ha, while the average yield of total carbon stocks was 973,31 tons/ha.Keyword: Rupat, Mangrove, Biomass, Carbon,